Front Cover: Ultrasensitive determination of highly polar trimethyl phosphate in environmental water by molecularly imprinted polymeric fiber headspace solid‐phase microextraction. Issue 5 (6th March 2018) - Cai, Cuicui; Zhang, Pengcheng; Deng, Jiali; Zhou, Hongbin; Cheng, Jing
Abstract : J Sep Sci 2018, 41, 1104–1111 DOI:10.1002/jssc.201701048 The cover picture shows the procedure for preparation of trimethyl phosphate molecularly imprinted polymer monolithic fiber in a 7 cm fused‐silica capillary tube, a graphic illustration of trimethyl phosphate molecular imprinting and removing process and a picture of the prepared trimethyl phosphate molecularly imprinted polymer monolithic fiber which can be bended.